Thermally Radiative Casson Fluid Flow over a Cylinder with Newtonian Heating and Heat generation/absorption. Issue 2 (July 2021) - Loganathan, K; Sivakumar, M; Mohanraj, M; Sakthivel, P
Abstract: This communication explains the impact of thermally radiative flow of a Casson fluid over a cylinder with velocity slip, suction/injection, and Newtonian heating condition. The governing PDE expressions are remodeled into an ODE expressing by applying suitable variables. The homotopy analysis (HAM) technique was implemented for solving our models. The impact of velocity field, temperature distribution, skin friction coefficient, Nusselt number in terms of diverse physical parameters like Casson parameter, suction/injection parameter, Newtonian heating parameter, radiation parameters, heat generation/absorption, Hartmann number and velocity slip parameter. The Hartmann number leads to slow down the fluid velocity, skin friction coefficient and local Nusselt number. The slip parameter decreases the fluid velocity and enhance the fluid heat transfer gradient.